(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify the level of electronic loafing among fourth-grade science students and to reveal the relationship between it and self-learning skills, The current research community consisted of fourth-grade Scientific students in the First Rusafa Education Directorate in Baghdad. The researcher took her sample of (400) male and female students distributed equally among (200) students from Abu Alaa Al-Ma’arri Preparatory School for boys and (200) female students from Al-Firdaws Preparatory School for girls in the Directorate of Education for the first Rusafa, for the second semester of the year (2024-2025). To achieve the research goal, the researcher prepared the research tools represented by the electronic loafing scale and the self-learning skills scale, as the electronic loafing scale consisted of (15) paragraphs distributed equally over three dimensions, which are ((Social Electronic loafing, recreational Electronic loafing, cognitive electronic loafing), and each paragraph has five alternatives according to the five-point Likert scale, which are (always applies to me, sometimes applies to me, rarely applies to me, a little applies to me, never applies to me), while the self-learning skills scale consisted of (20) paragraphs distributed equally over four areas (skills) for each skill (5) Paragraphs are (self-study planning skill, self-study skill, resource use skill, general and transferred skills), and each paragraph has five alternatives which are (applies to me to a great extent, applies to me to a medium extent, applies to me to a small extent, applies to me very little, does not apply to me), and the researcher verified the psychometric properties of the research tools represented by validity and reliability, and it was Validity was verified in two ways: (Construct validity and Face validity), and reliability was extracted in two ways: (retest) and (Cronbach’s alpha equation), where the reliability value of the electronic loafing scale reached (0.81) by the retest method, while the Cronbach’s alpha equation reached (0.855) for the loafing scale, while the reliability of the self-learning scale reached (0.88) by the retest method It reached (0.865) when using the Cronbach’s alpha equation, and after extracting the validity and reliability for each of them, the researcher applied the two scales to the sample and the results showed that the sample have electronic loafing and self-learning skills. The results also showed that there were no statistically significant differences between the sample members in terms of the gender variable in electronic loafing, and that there were no statistically significant differences for the sample In the gender variable in self-learning skills, with a positive direct relationship between the dimensions of electronic loafing and self-learning skills, and with these results, the researcher formulated some proposals, including conducting similar studies on electronic loafing among university students and on electronic loafing and its relationship to other variables, and the researcher recommends conducting training courses and workshops on how to Dealing with electronic loafing and Guiding and monitoring students’ purposeful use of technology.